Modelling oxygen effects on the in- and out-of-field radiosensitivity of cells exposed to intensity-modulated radiation fields. (7th May 2023) - Matsuya, Yusuke; McMahon, Stephen J; Butterworth, Karl T; Yachi, Yoshie; Saga, Ryo; Sato, Tatsuhiko; Prise, Kevin M
Abstract: Objective . The delivery of intensity-modulated radiation fields has improved the conformity of dose to tumour targets during radiotherapy (RT). Previously, it has been shown that intercellular communication between cells positioned in- and outside of the radiation field impacts cellular radiosensitivity under hypoxic and normoxic conditions. However, the mechanism of intercellular communication in hypoxia remains to be fully understood. In this study, the cell-killing effects of intercellular communication in hypoxia were modelled in an effort to better understand the underlying mechanisms of response. Approach . By irradiating a 50% area of the culture dish (half-field exposure), experimental dose-response curves for cell survival and residual DNA double-strand breaks (DSBs) were generated in prostate (DU145) and non-small cell lung cancer (H1299) cells. The oxygen enhancement ratio (OER) was determined from early DSB yields (corresponding to relative direct damage) and used to model the in- and out-of-field radiosensitivity. Main results . The developed integrated microdosimetric-kinetic (IMK) model successfully predicted the experimental dose responses for survival and lethal lesions, and provides a mechanistic interpretation that the probability of hits for releasing cell-killing signals is dependent on oxygen. This experimental and modelling study also suggests that residual DSBs correspond to logarithmic survival fraction (meaning lethal lesions) for in- and out-of-field cells. Our data suggest that the OER value determined using uniform-field exposure can be applied to predict the in- and out-of-field radiosensitivity of cells following exposure to intensity modulated beams. Significance . The developed IMK model facilitates a more precise understanding of intercellular signalling following exposure to intensity-modulated radiation fields.